A guide to reading & writing Japanese : (Charles E. Tuttle Co., 1959)
This book is designed first of all to make the study of written Japanese a much less formidable task for the foreign student than it has traditionally been. Its second major purpose is to enable the student to achieve fluency in reading and writing the language in its everyday style. Essentially, the book reflects the language simplification movement now under way in Japan.